Insurance Premiums and Insurance Coverage of Near-Poor Children - Jack Hadley; James D. Reschovsky; Peter Cunningham; Genevieve Kenney; Lisa Dubay (SAGE Publishing, 2006)
States increasingly are using premiums for near-poor children in their public insurance programs (Medicaid/SCHIP) to limit private insurance crowd-out and constrain program costs. Using national data from four rounds of the Community Tracking Study Household Surveys spanning the seven years from 1996 to 2003, this study estimates a multinomial logistic regression model examining how public and private insurance premiums affect insurance coverage outcomes (Medicaid/SCHIP coverage, private coverage, and no coverage). Higher public premiums are significantly associated with a lower probability of public coverage and higher probabilities of private coverage and uninsurance; higher private premiums are significantly related to a lower probability of private coverage and higher probabilities of public coverage and uninsurance. The results imply that uninsurance rates will rise if both public and private premiums increase, and suggest that states that impose or increase public insurance premiums for near-poor children will succeed in discouraging crowd-out of private insurance, but at the expense of higher rates of uninsurance. Sustained increases in private insurance premiums will continue to create enrollment pressures on state insurance programs for children.